The Dynamics of Indonesian Muslim Spirituality in the United States - Supardi, Bambang Irawan (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2024)
This article discusses the dynamics of spirituality among Indonesian Muslims who have migrated to the United States, focusing on how they maintain and express their religious identity within a diverse society. The research analyzes the challenges faced by the Indonesian Muslim community in preserving spiritual practices in culturally and socially different environments. Additionally, the article explores the role of community, religious organizations, and technology in supporting the sustainability of their spirituality. The findings indicate that Indonesian Muslims in the United States experience a transformation in their religious practices, often involving adaptation and innovation to keep their spiritual identity alive. This article provides insights into how the Indonesian Muslim diaspora shapes their religious identity abroad and contributes to spiritual diversity in the United States.